Possible Benefits of Faecalibacterium prausnitzii for Obesity-Associated Gut Disorders - Maioli, Tatiani Uceli; Borras-Nogues, Esther; Torres, Licia; Barbosa, Sara Candida; Martins, Vinicius Dantas; Langella, Philippe; Azevedo, Vasco Ariston; Chatel, Jean-Marc (Frontiers in Pharmacology, 2021)
Metabolic disorders are an increasing concern in the industrialized world. Current research has shown a direct link between the composition of the gut microbiota and the pathogenesis of obesity and diabetes. In only a few weeks, an obesity-inducing diet can lead to increased gut permeability and microbial dysbiosis, which contributes to chronic inflammation in the gut and adipose tissues, and to the development of insulin resistance. In this review, we examine the interplay between gut inflammation, insulin resistance, and the gut microbiota, and discuss how some probiotic species can be used to modulate gut homeostasis. We focus primarily on Faecalibacterium prausnitzii, a highly abundant butyrate-producing bacterium that has been proposed both as a biomarker for the development of different gut pathologies and as a potential treatment due to its production of anti-inflammatory metabolites.